REGULATORY FACILITATION AS AN EFFORT FOR LEGAL PROTECTION OF CHILD RIGHTS RELATED TO CHILD MARRIAGE - Nany Suryawati (Novateur Publications, 2023)
Observing the norms that live in society in the State of Indonesia, it becomes a matter of pride for the noble values contained in these norms, which are called: habits in society. All aspects of community life are well regulated and accompanied by agreement as well as adherence to these values, especially regarding values in forming a prosperous family and upholding respect for elders in carrying out activities and actions for the continuity of the family. Therefore, as an effort to maintain the continuity of the family, both girls and boys are prepared to form a new family. Based on the results of research using normative juridical methods supported by interviews with several tribes, surprising data was obtained, that forming a new family was prioritized for carrying out marriages at a young age (children) without regard to their physical and mental readiness. Because the State of Indonesia is a constitutional state, and marriage is also regulated in a law which has stipulated the conditions for a marriage which include the age requirement to be ready to form a new family, it is necessary for the government to intervene strictly. as one of the government's efforts to prevent child marriage. Laws that have existed so far can be considered not fully complied with and ineffective in their implementation, so it is necessary to involve the community, among other things, by facilitating arrangements in legal reform, particularly the marriage law. It is hoped that the facilitation of this regulation can prevent the occurrence of young marriages (children) in the community, so that the continuity of the family which is also the Indonesian nation can improve the quality of Indonesian people evenly, so that various efforts are needed to be made so that this goal can be achieved. This government effort is carried out by involving the community through community leaders (traditional leaders, religious leaders, other leaders), with effective and efficient outreach to the community
Keywords: Regulatory Facilitation; Young (Child) Marriage